2003
DOI: 10.3121/cmr.1.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Polyps

Abstract: Describe the current general classification of colon polyps. Which features of an adenomatous polyp correlate with greater malignant potential? Colorectal polyps are classified histologically as neoplastic or non-neoplastic (Table 1). The majority of polyps are small, non-neoplastic lesions that are found during screening or when procedures are performed for other diagnostic reasons (for example, a gastrointestinal bleed). The malignant potential and subsequent screening intervals are dependent on polyp type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 7 publications
0
30
1
3
Order By: Relevance
“…Within adenomas, the proportion of villous type -a direct precursor of CRC -increased remarkably with age. Further, adenomas found in older patients had in ~56% of cases high-grade dysplasia and were > 1 cm large (both indicators of a high malignant potential) (11). A direct comparison of our findings with previous studies is challenging due to differences with regard to study period and population (in terms of age, gender and ethnicity).…”
Section: Discussioncontrasting
confidence: 46%
“…Within adenomas, the proportion of villous type -a direct precursor of CRC -increased remarkably with age. Further, adenomas found in older patients had in ~56% of cases high-grade dysplasia and were > 1 cm large (both indicators of a high malignant potential) (11). A direct comparison of our findings with previous studies is challenging due to differences with regard to study period and population (in terms of age, gender and ethnicity).…”
Section: Discussioncontrasting
confidence: 46%
“…The framework of sporadic colorectal cancer is the adenoma–carcinoma sequence, describing the change from histologically normal cells to pre-malignant adenomatous epithelium exhibiting increasing degrees of cell dysplasia to overt invasive malignant disease (Fearon and Vogelstein, 1990; Leslie et al , 2002). The pre-malignant phenotype, colorectal adenomatous polyps, exerts characteristics that denote high-malignant potential, such as increasing size, increasing degree of cell dysplasia and greater villous content (O'Brian et al , 1990; Colucci et al , 2003; Giuliani et al , 2006). These features are central to the current guidelines on patient management and specifically interval of surveillance colonoscopy (Cairns et al , 2010).…”
mentioning
confidence: 99%
“…Our results showed that miR-137 is down-regulated in colon polyps, supporting the conclusion of the early silencing of miR-137 in colorectal adenoma. According to the histological studies, colorectal polyps can be simply classified into two groups–non-neoplastic and neoplastic polyps–according to their malignant potency [30]. Importantly, the expression level of miR-137 is gradually decreased in hyperplastic, tubular and villous polyps (Figure 7B and Table 3).…”
Section: Discussionmentioning
confidence: 99%